Fe3+-Sensitive Carbon Dots for Detection of Fe3+ in Aqueous Solution and Intracellular Imaging of Fe3+ Inside Fungal Cells - Chen, Yanqiu; Sun, Xiaobo; Pan, Wei; Yu, Guifeng; Wang, Jinping (Frontiers in Chemistry, 2020)
In this article, the Fe3+-sensitive carbon dots were obtained by means of a microwave-assisted method using glutamic acid and ethylenediamine as reactants. The carbon dots exhibited selective response to Fe3+ ions in aqueous solution with a turn-off mode, and a good linear relationship was found between (F0-F)/F0 and the concentration of Fe3+ in the range of 8–80 μM. As a result, the as-synthesized carbon dots can be developed as a fluorescent chemosensor for Fe3+ in aqueous solution. Moreover, the carbon dots can be applied as a fluorescent agent for fungal bioimaging since the fungal cells stained by the carbon dots were brightly illuminated on a confocal microscopy excited at 405 nm. Furthermore, an increase in the concentration of intracellular Fe3+ could result in fluorescence quenching of the carbon dots in the fungal cells when incubated in the Tris-HCl buffer solution containing Fe3+. However, due to EDTA might hinder Fe(III) to enter the fungal cells, incubation in Fe(III)-EDTA complex solution exerted negligible effect on the fluorescence of fungal cells labeled by the carbon dots. Therefore, the carbon dots can serve as a potential probe for intracellular imaging of Fe3+ inside fungal cells.